Technologies for Enhancing Students' Digital Competence in Teaching English - Toshboyeva Barno Odilovna; Dadakhanova Mohlaroyim (Zien Journals, 2023)
This research study investigates the implementation of various technologies to foster the development of students' digital competence in the context of teaching English. In an increasingly digitalized world, it is essential for students to acquire the necessary skills and knowledge to effectively navigate and communicate in digital environments. The purpose of this research is to explore the potential of specific technological tools and strategies in enhancing students' digital competence in the domain of English language learning. The findings of this study will contribute to the existing body of knowledge regarding technology integration in education and provide valuable insights for educators
Keywords: digital competence; technology integration; English language teaching